PENGARUH PENDIDIKAN KESEHATAN ROM TERHADAP TINGKAT PENGETAHUAN DAN KETERAMPILAN ROM KELUARGA PENDERITA STROKE - Sulistyawati, Sulistyawati; Fitriana, Nurul Fatwati (Nursing Sciences Journal, 2024)
The family plays a significant role in the recovery phase of stroke patients. Stroke patients experience muscle weakness that hinders their ability to perform daily activities. One approach to assist in recovery is ROM. Educating the families of patients about ROM is essential to enhance their knowledge and skills, enabling them to support the patient's recovery process. This study aims to determine the impact of ROM health education on the knowledge and skills of families of stroke patients at RSUD Prof. Dr. Margono Soekarjo Purwokerto. A quasi-experimental design with a one-group pretest-posttest was used. A sample of 39 participants was selected through purposive random sampling. Data were collected using questionnaires and observation sheets. Data analysis was performed using the dependent t-test. The respondents' minimum knowledge level before and after education  was 9-12. The respondents' minimum skill level before and after education was 2-7. There was a significant impact of ROM education on the knowledge of families of stroke patients and also on the ROM skills of families of stroke patients (p = 0.001). ROM education significantly influences the knowledge and skills of families of stroke patients.